Inflation - Interest Rate - Exchange Rate Dilemma: Turkish Reality During The GEG Program - ÖZDEMİR YAZGAN, SELİN DEVRİM; AKGÜL, ŞEVKET IŞIL (EGE UNIV, FAC ECONOMICS & ADMIN SCIENCES, 2018)
This study aims to bring out whether the Central Bank's or politicians statements are valid on the relationships between both interest rate and inflation rate and exchange rate and inflation rate. Analyzing period covers the period between 2006 and 2013 so as to cover program for Turkey's Transition to Strong Economy. Furthermore analysis are made for two sub-periods in concordance with breakdown dates, and the causality between both interest rate and inflation rate and exchange rate and inflation rate is examined for each sub periods. The analysis of above mentioned relationships for the variables which are determined stationary but non-linear is implemented by Diks-Panchenko non-linear causality test. After the analysis we find that there are sub-periods in which both two ideas are valid or there are sub-periods only one idea is valid. Findings can be a guide and provide important information to the policy makers how to deal with the relationships between economic variables.
Keywords: Inflation Rate; Interest Rate; Exchange Rate; Nonlinear Causality; Diks-Panchenko Causality Test; UNIT-ROOT; DOLLAR; PRICES; TESTS